ALIENAÇÃO, REIFICAÇÃO E FETICHE DA MERCADORIA: Experiência da vida cotidiana e filosofia em sala de aula" - Jonathan Rodrigues Louveira (2022)
The present dissertation aims to analyze and develop in the classroom aspects of the dialetic of everyday life developed by Karl Marx, and later also worked on by Karel Kosik, Agnes Heller, Henri Lefebvre, among others. Knowing and developing aspects of this philosophy can be of great value for the analysis and change of concrete reality in everyday life. Everyday life is a world in which the human being lives and develops, when we are born it is already imposed on us, it is something given, but it does not mean that it cannot be changed, both in relation to the individual aspect and the social aspect. Everyday life hides the world of pseudo-concreteness, also known as fetishized práxis in Marxist language, a world of appearances, of mechanized actions. Through a deviation (détour), this is the analysis and reflection on the reality of everyday life, on a materialistic perspective. This deviation from everyday life can be operated through philosophy, art and literature. This deviation must seek more transparent and egalitarian daily relations, seeking to dissipate the alienation and antagonisms imposed by capitalist society, which reduces human relations to product relations, the reification of merchandise to the detriment of the human.